ANALISIS STRATEGI PEMASARAN PERUSAHAAN DAGANG DALAM MENINGKATKAN PENJUALAN DI KOTA PADANGSIDIMPUAN - Lilis Saryani; Ahmad Sayuti Pulungan; Nursalamah (Yayasan Perguruan Kampus, 2026)
In this era of globalization, economic development has progressed in the activities of companies operating in the marketing sector, particularly trade. Trading companies are required to implement effective marketing strategies to increase sales and maintain their existence. Marketing strategy is crucial for a company, as it is the key to determining appropriate steps to meet sales targets and achieve competitive advantage. This study aims to analyze marketing strategies that trading companies can use to increase sales. The method used in this study is a qualitative approach. The data sources used are secondary data, which is data collected indirectly, not from original sources, but rather data sourced from magazines or journals, and data from the internet. Based on the results of the analysis, it shows that effective marketing strategies implemented by a company are market segmentation, targeting, positioning, marketing mix, SWOT analysis, and digital marketing. By implementing these strategies, the company can increase sales and build a competitive advantage.